The African American theatrical body : reception, performance, and the stage - Colbert, Soyica Diggs (Cambridge University Press, 2011)
"Presenting an innovative approach to performance studies and literary history, Soyica Colbert argues for the centrality of black performance traditions to African American literature, including preaching, dancing, blues and gospel, and theatre itself, showing how these performance traditions create the 'performative ground' of African American literary texts. Across a century of literary production using the physical space of the theatre and the discursive space of the page, W. E. B. Du Bois, Zora Neale Hurston, James Baldwin, August Wilson and others deploy performances to re-situate black people in time and space. The study examines African American plays past and present, including A Raisin in the Sun, Blues for Mister Charlie and Joe Turner's Come and Gone, demonstrating how African American dramatists stage black performances in their plays as acts of recuperation and restoration, creating sites that have the potential to repair the damage caused by slavery and its aftermath"--